Symposium 1: Tracing analytic assemblages – doing doctoral research with actor-network theory - Mörtsell, Sara (Proceedings of the International Conference on Networked Learning, 2024)
The practices of doctoral education are intricately entangled with technologies. This methodological paper examines the practical concerns involved in doing the analytic work in a networked learning setting with Actor-Network theory (ANT). It is a story about engaging with ANT as a companion in an ethnographic research project on teaching practices in Sweden during the Covid-19 pandemic. The empirical examples are pulled from online interviews in the pandemic outbreak and two ways of assembling the analytic practices of those interviews. On the premises that method and technology are non-neutral, the focus is on how the interviews are analysed and the modes of knowing that they form. For example, the paper examines how computer-assisted qualitative data analysis software acts on the analyses of the interviews and the knowledge patterns made possible and what signals are silenced. A second analytic assemblage is deployed that traces those signals. Based on the empirical examples of doing analyses, the paper discusses how analytic assemblages change and move research and the researcher in unpredictive and performative ways that troubles the expectations of a singularised doctoral journey.